Handbook of ethical and social issues in knowledge management: Organizational innovation - Costa, Gonçalo Jorge Morais da (2014)
Knowledge management is a multi-disciplinary field, encompassing management, information science, psychology, sociology, neurobiology, ethics, and others. It impacts many organizational communities, which determine its boundaries, making ethical and social dilemmas vital it is proper execution. Ethical Issues and Social Dilemmas in Knowledge Management: Organizational Innovation considers these dilemmas at two levels: the individual vs. individual and the individual vs. the collective, providing a thorough treatment of these facets. This book demonstrates the philosophical underpinnings of each dimension of knowledge management, exposing the ethical and social dilemmas that occur. It also links knowledge management and organizational innovation and proposes and explores strategies to minimize such dilemmas. This book clearly illustrates a whole new perspective on knowledge management, as well as expanding the literature treating this approach.